Detection of specific IgG, IgM, IgE and IgG subclass antibodies for serological diagnosis of human cystic echinococcosis - Naik M. I.; Tenguria R. Kumar; Haq Ehtishamul (Helminthologia, 2015)
An enzyme linked immunosorbent assay (ELISA), based on sheep hydatid cyst fluid antigen was used for the detection of specific antibodies of IgG, IgM, IgE and IgG subclass in the serum samples of 62 clinically and radiologically diagnosed cystic echinococcosis (CE) patients, 8 clinically suspected cases of CE, 25 other parasitic disease controls and 25 healthy controls. The diagnostic sensitivity in the clinically and radiologically suggestive cases (n = 62) for IgG antibody detection was highest (93 %), followed by IgE, IgG4, IgG1, IgG2, IgM and IgG3 with 89 %, 87 %, 85 %, 76 %, 70 % and 55 % respectively. The detection of specific IgE, IgG1 and IgG4 antibody showed the higher diagnostic sensitivity and specificity to the extent that they can be safely used as better substitute to IgG. Even though, the diagnostic sensitivity of IgG was highest (93%) but was less specific (88 %) due to the frequent non-specific reactions in the sera of patients with other parasitic infections and healthy controls. None of the sera samples from healthy controls gave non-specific reaction with IgE, IgG1 and IgG4 and there was a considerably reduced cross-reaction with these antibodies. The most discriminatory and specific antibodies found in this study belonged to IgE, IgG1 and IgG4; therefore, these antibodies may serve as useful diagnostic markers for CE.